Antiproliferative activity of ionic liquid-graviola fruit extract against human breast cancer (MCF-7) cell lines using flow cytometry techniques - Daddiouaissa, Djabir; Amid, Azura; Kabbashi, Nassereldeen Ahmed; Ahmad Fuad, Fazia Adyani; Elnour, Ahmed; Epandy, Mohamad A.K.M S. (Elsevier Ireland Ltd, 2019)
Ethnopharmacological relevance Medicinal plants have been used for ages by indigenous communities around the world to help humankind sustain its health. Graviola (Annona muricata), also called soursop, is a member of the Annonaceae family and is an evergreen plant that is generally distributed in tropical and subtropical areas of the world. Graviola tree has a long history of traditional use due to its therapeutic potential including anti-inflammatory, antimicrobial, antioxidant, insecticide and cytotoxic to tumor cells.